2022
DOI: 10.1007/s12016-021-08909-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence, Inflammaging, and Frailty: Role of Myeloid Cells in Age-Related Diseases

Abstract: The immune system is the central regulator of tissue homeostasis, ensuring tissue regeneration and protection against both pathogens and the neoformation of cancer cells. Its proper functioning requires homeostatic properties, which are maintained by an adequate balance of myeloid and lymphoid responses. Aging progressively undermines this ability and compromises the correct activation of immune responses, as well as the resolution of the inflammatory response. A subclinical syndrome of “homeostatic frailty” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 274 publications
(388 reference statements)
2
50
0
2
Order By: Relevance
“…The combination of these events contributes to an enhanced status of inflammaging and may be a possible explanation for the greater susceptibility of the older people to invasive bacterial infections [ 23 ]. The majority of these events can be detected following in vitro stimulation with formyl-methionine-leucine-phenylalanine, lipopolysaccharide (LPS), and granulocyte–macrophage colony-stimulating factor (GM-CSF) [ 26 ].…”
Section: Immunosenescence Of the Innate Immune Cellsmentioning
confidence: 99%
“…The combination of these events contributes to an enhanced status of inflammaging and may be a possible explanation for the greater susceptibility of the older people to invasive bacterial infections [ 23 ]. The majority of these events can be detected following in vitro stimulation with formyl-methionine-leucine-phenylalanine, lipopolysaccharide (LPS), and granulocyte–macrophage colony-stimulating factor (GM-CSF) [ 26 ].…”
Section: Immunosenescence Of the Innate Immune Cellsmentioning
confidence: 99%
“…In addition, a recent study revealed that aging alters critical pathways important in the production of type I interferon in CD14 dim CD16 + monocytes, resulting in impaired innate immune responses to pathogen recognition receptor (PRR) agonists [ 108 ]. The frequency of circulating myeloid-derived suppressor cells (MDSCs) increases with age in both humans and mice [ 109 ]. Interestingly, proinflammatory factors produced by senescent cells promote both the proliferation and activation of MDSCs, which, in turn, secrete the anti-inflammatory cytokine TGF-β, a potent inducer of cellular senescence in inflamed tissues [ 110 ].…”
Section: Aging and Immunosenescencementioning
confidence: 99%
“…Among these factors, IL-1, IL-6 and TNF-α remarkably support cancer growth and spreading (Jobe et al 2016;Bleve et al 2022;Strnadová et al 2022). IL-6 represents a direct link between autoimmune disorders, cancer and age-related diseases, thus offering an attractive therapeutic target (Iorio et al 2021).…”
Section: Role Of Il-6 and Other Inflammation-supporting Factorsmentioning
confidence: 99%